1989
DOI: 10.1085/jgp.94.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-induced calcium release mechanism in guinea pig taenia caeci.

Abstract: Fura-2 was used to measure the amount of Ca released from the intracellular Ca store of a saponin-skinned smooth muscle fiber bundle of the guinea pig taenia caeci (width, 150-250 #m) placed in a capillary cuvette at 20-22~ The amount of Ca actively loaded into the store was assayed when released by the application of 50 mM caffeine and/or 10 #M inositol 1,4,5-trisphosphate (IPs) in the absence of ATP, and was found to have a biphasic dependence on the loading [Ca ~+] with a peak near pCa 6. After Ca loading a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
144
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(152 citation statements)
references
References 37 publications
8
144
0
Order By: Relevance
“…Details of the method are described elsewhere (Iino, 1989;Ikemoto et al, 1995;1996). Brie¯y, thin bundles ®xed in a capillary cuvette were mounted on the stage of a microscope (BHS-RFK, Olympus, Tokyo, Japan) equipped with a¯uorometer (CAM-200, Nihon Bunko Kogyo, Tokyo, Japan) for the measurement of the¯uorescence intensity of Fura-2 at 510 nm with alternating 340 and 380 nm excitations.…”
Section: Measurement Of Ca 2+ Release In Skinned Fibresmentioning
confidence: 99%
“…Details of the method are described elsewhere (Iino, 1989;Ikemoto et al, 1995;1996). Brie¯y, thin bundles ®xed in a capillary cuvette were mounted on the stage of a microscope (BHS-RFK, Olympus, Tokyo, Japan) equipped with a¯uorometer (CAM-200, Nihon Bunko Kogyo, Tokyo, Japan) for the measurement of the¯uorescence intensity of Fura-2 at 510 nm with alternating 340 and 380 nm excitations.…”
Section: Measurement Of Ca 2+ Release In Skinned Fibresmentioning
confidence: 99%
“…The Ca¥ released from the permeabilized fibres was quantified using fura_2 (Grynkiewicz, Poenie & Tsien, 1985). Further details of the method are described elsewhere (Iino, 1989). Briefly, thin bundles were mounted in a capillary cuvette.…”
Section: Measurement Of Ca¥ Release In Permeabilized Fibresmentioning
confidence: 99%
“…The cuvette was mounted on the stage of a microscope (BHS-RFK, Olympus, Tokyo) equipped with a fluorometer (CAM-200, Nihon Bunko Kogyo, Tokyo) for the measurement of the fluorescence intensity of fura_2 at 510 nm with alternating 340 and 380 nm excitations at room temperature (21-23°C). The SR of permeabilized fibres was actively loaded with Ca¥ for 120 s in a loading solution containing 0·2 ìÒ Ca¥ buffered with 10 mÒ EGTA and 4 mÒ MgATP (Iino, 1989), and then the experimental solution was changed to one not containing Ca¥ and MgATP. Finally, a Ca¥ releasing stimulus was applied in the presence of 35 ìÒ fura_2.…”
Section: Measurement Of Ca¥ Release In Permeabilized Fibresmentioning
confidence: 99%
“…This indicates that the resveratrol has an inhibitory effect on the release of Ca 2+ from the intracellular pools induced by stimulation of muscarinic ACh receptors, which is weakly responsible for the secretion of CA. It has been shown that Ca 2+ -uptake into intracellular storage sites susceptible to caffeine (Ilno, 1989) is almost completely abolished by treatment with cyclopiazonic acid during the proceeding of Ca 2+ load (Suzuki et al, 1992). This is consistent with the findings obtained in exposed smooth muscle fibers of the longitudinal layer of the guinea-pig ileum, where Ca 2+ -uptake was also inhibited by cylopiazonic acid (Uyama et al, 1992).…”
Section: Discussionmentioning
confidence: 99%